COMPETİTİVE POWER OF TURKİSH AGRİCULTURAL PRODUCTS AND GOVERNMENT SUPPORTS İN TURKİSH AGRİCULTURAL SECTOR (Third Sector Social Economic Review, 2020)
The agricultural sector is a sector of strategic importance in Turkey as it is all over the world. In particular, the Covid-19 Pandemic has revealed how important the agricultural sector, food security and the support made by states to the agricultural sector are. For this reason, countries around the world have taken important steps to protect and support the domestic agricultural sector more or less from past to present. In the study, the competitive power of Agricultural products with Harmonized Codes 06-21 in Turkey against OECD countries of which 37 countries are members was analyzed to cover the years 2013-2019. Comparative Export Performance Index was used in the study. As a result of the analysis, Turkey had no competitiveness against OECD countries in six of the 16 product groups included in the study, that the competitiveness of all five product groups had a weak comparative advantage, and that all four product groups had a moderately comparative advantage of competitiveness and had a strong comparative advantage in one product group. According to the findings obtained as a result of the study, it was discussed how statesupports for the existing agricultural sector should be for Turkey.
Keywords: Agriculture Sector; Competitiveness; Agricultural Government Supports